Odpowiedzi

2009-12-01T15:59:34+01:00
2 2
c)4y - 8y + 3y - 6 - 8y - 4y = 3y - 6
reszty niepotrafie niestety:)


2009-12-01T16:03:27+01:00
C) 4y² - 8y + 3y - 6 - 8y + 4y² = 8y² - 12y -6
d) -3c² + 3c + 2c - 2 - c² + 2c = -4c² + 7c - 2
e) 6a² - 2 - a² - 2a - 2a - 4 = 5a² - 6 - 4a
f) 5x⁴ + 5x² - x⁴ - 3x² + 2x² + 6 = 4x⁴ + 4x² + 6
2009-12-01T16:15:48+01:00
C)(4y+3)(y-2)-2y(4-2y)=4y²-8y+3y-6-8y+4y²=-13y+8y²-6
d)-(3c-2)(c-1)-c(c-2)=-(3c²-3c-2c+2)-c²+2c=-3c²+3c+2c-2-c²+2c=7c-4c²-2
e)2(3a²-1)-(a+2)(a+2)=6a²-2-(a²+2a+2a+4)=6a²-2-a²-2a-2a-4= -4a+5a²-4
f)5x²(x²+1)-(x²-2)(x²+3)=5x⁴+5x²-(x⁴+3x²-2x²-6)=5x⁴+5x²-x⁴-3x²+2x²+6= 4x²+4x⁴+6